APLIKASI KAMUS ELEKTRONIK BAHASA ISYARAT BAGI TUNARUNGU DALAM BAHASA INDONESIA BERBASIS WEB - Yuli Fauziah; Bambang Yuwono; Cornelius DWP (Jurusan Teknik Informatika, 2012)
Communication is the key to conquering this globalization era. And there is no doubtthat the language is the most important part of communication. One can communicate wellwhen using the same language or understanding the language used to each other.Signlanguage is the language of communication priority manually, body language and lip motion incommunicating. Sign language has been standardized by the name Sibi (Cue SystemIndonesian). Sibi is one of the media in the form of books, can help communication among thedeaf in the community. His form is setting a systematic set of fingers, hands, and othermovements that symbolize Indonesian vocabulary. Media book seems less easily understoodby the user, so the need for an application that is able to provide an image that is moving,making it easier to learn the sign language.Keywords: Communication, Systems cues Indonesian language, Sign Language